SPEECH SYNTHESIZER BASED ON THE PROJECT MBROLA - Rajs, Arkadiusz; Banaszak-Piechowska, Agnieszka; Drzycimski, Paweł (Journal of Education, Health and Sport, 2015)
Rajs Arkadiusz, Banaszak-Piechowska Agnieszka, Drzycimski Paweł. Speech synthesizer based on the project MBROLA. Journal of Education, Health and Sport. 2015;5(12):160-164. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35266 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A160-164 http://pbn.nauka.gov.pl/works/678876 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 25.11.2015. Accepted: 10.12.2015. SPEECH SYNTHESIZER BASED ON THE PROJECT MBROLA PhD. Arkadiusz Rajs University of Science and Technology in Bydgoszcz Faculty of Telecommunications and Electrical Engineering, Al. Prof. S. Kaliskiego 7, 85-796 Bydgoszcz, arajs@utp.edu.pl PhD. Agnieszka Banaszak-Piechowska Institute of Physics, Faculty of Mathematics, Physics and Technique Science, Kazimierz Wielki University, 85-052 Bydgoszcz, Powstańców Wlkp. 2, agnb@ukw.edu.pl Eng. Paweł Drzycimski student, University of Science and Technology in Bydgoszcz Faculty of Telecommunications and Electrical Engineering, Al. Prof. S. Kaliskiego 7, 85-796 Bydgoszcz, pdrzycimski@gmail.com Summary: Speech synthesizers find wider application in IT systems to ensure easy Communications with the Man and machine. In this article focused on speech synthesizer of polish language realization based on international project MBROLA. Keywords: speech synthesizers, IT systems, man, machine, polish language, MBROLA.